Activating the Antibacterial Effect of 4, 6‐Diamino‐2‐pyrimidinethiol‐Modified Gold Nanoparticles by Reducing their Sizes. Issue 52 (14th December 2020) - Xie, Yangzhouyun; Yang, Junchuan; Zhang, Jiangjiang; Zheng, Wenfu; Jiang, Xingyu
Abstract: Adequately decorated gold nanoparticles (GNPs) have excellent antibiotic activities against multidrug‐resistant (MDR) bacteria. Nanoparticles exhibiting Gram selective antibacterial actions are beneficial to precise therapy. Here, we present a strategy to tune the antibacterial spectrum of a small molecule (4, 6‐diamino‐2‐pyrimidinethiol, DAPT)‐modified GNPs (DAPT‐GNPs, DGNPs) by adjusting their sizes. Compared to large (ca. 14 nm diameter) DGNPs (lDGNPs) and medium‐sized (3–4 nm diameter) DGNPs (mDGNPs), which have no antibacterial effect or only target Gram‐negative (G−) bacteria, ultrasmall DGNPs (uDGNPs, <2 nm) have a broad antibacterial spectrum, especially showing an over 60‐fold increase in antibacterial efficacy against Gram‐positive (G+) bacteria. Moreover, the uDGNPs‐functionalized scaffolds (agarose gel) can serve as general wound dressings for healing burnt infections. Our strategy is insightful for exploring properties of the nanomaterials and their applications. Abstract : 4, 6‐Diamino‐2‐pyrimidinethiol (DAPT)‐modified gold nanoparticles (DGNPs) possess spectrum‐adjustable antimicrobial activity by changing their sizes. The ultrasmall DGNPs‐embedded scaffolds show excellent performance in treating burn wound infections on rats and are promising for clinical applications.